2007
DOI: 10.1542/peds.2006-2841
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Prevention of Hydrocephalus After Intraventricular Hemorrhage in Preterm Infants: Brain-Washing Versus Tapping Fluid

Abstract: Despite its logical basis and encouraging pilot data, drainage, irrigation, and fibrinolytic therapy did not reduce shunt surgery or death when tested in a multicenter, randomized trial. Secondary intraventricular hemorrhage is a major factor that counteracts any possible therapeutic effect from washing out old blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 23 publications
1
92
1
4
Order By: Relevance
“…Thirty-five percent (12 of 34) of preterm infants in the DRIFT study had secondary IVH, compared with 8% (3 of 34) who received standard treatment. 71 These results differ from those of earlier Class II and Class III studies in which a decreased rate for the need for permanent shunt placement was reported when low-dose urokinase or fibrinolytic therapy with tPA was used for ventricular irrigation and clot reduction. 32,61,75,77 Reviews conducted by Whitelaw and Odd 74 have also revealed that intraventricular injection of streptokinase has not been shown to be beneficial.…”
Section: Nonsurgical Temporizing Agentscontrasting
confidence: 93%
See 1 more Smart Citation
“…Thirty-five percent (12 of 34) of preterm infants in the DRIFT study had secondary IVH, compared with 8% (3 of 34) who received standard treatment. 71 These results differ from those of earlier Class II and Class III studies in which a decreased rate for the need for permanent shunt placement was reported when low-dose urokinase or fibrinolytic therapy with tPA was used for ventricular irrigation and clot reduction. 32,61,75,77 Reviews conducted by Whitelaw and Odd 74 have also revealed that intraventricular injection of streptokinase has not been shown to be beneficial.…”
Section: Nonsurgical Temporizing Agentscontrasting
confidence: 93%
“…71 DRIFT did not significantly reduce shunt surgery or death, but it was associated with an increased rate of secondary IVH (Table 3). 71 Forty-four percent (15 of 34) of infants in the DRIFT group died or required a shunt, compared with 50% (19 of 36) of infants who received standard treatment. Thirty-five percent (12 of 34) of preterm infants in the DRIFT study had secondary IVH, compared with 8% (3 of 34) who received standard treatment.…”
Section: Nonsurgical Temporizing Agentsmentioning
confidence: 97%
“…This smaller group of patients generally has a poorer neurodevelopmental outcome than either healthy controls or IVH patients who did not undergo shunt insertion [25, 26]. Nevertheless, aggressive measures to prevent the development of hydrocephalus after IVH including drainage, irrigation and fibrinolytic therapy provided no benefit in either the frequency of shunt surgery or the overall mortality [27]. Neurological outcome expectedly depends on the severity of IVH, with lesser dependence on birth weight and gestational age [28], though the long-term functional status of these patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They hope that therapy is going to reduce in antifibrolitic therapy to reduce the clot and normalizing the circulation of cerebrospinal fluid (18,54). Whitelaw opposes the use of streptokinase in infants with IVH (52). Therefore it remains as the basis of the surgical treatment.…”
Section: Discussionmentioning
confidence: 99%